EKSISTENSI HAK NON KEBENDAAN DALAM UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERNIKAHAN DAN HUKUM ISLAM - Arsan, A.Varadiba Maywardana; Sari, Muspita (IAIN Palopo, 2024)
The existence of non-material rights exists and is regulated in Islamic Law and Law no. 1 of 1974 concerning Marriage. In Islamic Law, non-material rights are regulated, for example, the wife's non-material rights, the husband is obliged to educate his wife to be religious, the husband has the best relationship with his wife and the husband is obliged to look after his wife. Then the husband's non-material rights, the wife is obliged to look after herself and her husband's property, not to make a sour face in front of her husband and not to do anything that her husband doesn't like. Furthermore, in Law no. 1 of 1974 non-material rights are regulated in Articles 30 to Article 34. According to Islamic Law, these non-material rights or rights and obligations are terminated if the wife applies nusyuz to her husband as well as the husband who applies nusyuz to his wife. Apart from that, a husband's obligations are terminated if he acts cruelly towards his wife. Meanwhile in Law no. 1 of 1974 non-material rights or rights and obligations. If the husband and wife are negligent in their rights and obligations, each can file a lawsuit with the Court as in Article 34 paragraph (3). Keywords: Existence, Non-Intangible Rights, Islamic Law